PHYSICAL EDUCATION IN SCHOOL NIGHT AND HEALTH PROMOTION (Fiep Bulletin - online, 2013)
Physical Education is undoubtedly of paramount importance for the development of the human being. However physical education in high school night, has been hampered by Law. 9.394/96, paragraph 3, item I, to provide the student the right to decide to participate or not, the Physical Education classes. Thus, this research seeks to raise the profile of the high school student night, the city of Ponta Grossa, PR, relating his work with the Physical Education in school. The methodology for this research was descriptive analysis quantiqualitative, being used for the methodological tool, a semi-structured questionnaire with seven questions to answer yes or no, with the participation of 136 middle school students overnight. It was concluded that 63.23% of students are those who were employed in counter-round school, and 65.11% did not agree with the law presented, and the student has the same right not to participate in physical education classes , 91.17% actively participate.
Keywords: Promoting Health; Physical Education; Secondary Education.